Mukhamandapa (front porch) and mandapa (pillared hall) of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
View of the mukhamandapa (front porch) and mandapa (pillared hall) of the Suhaveshwar Temple from the east and the southeast sides. The semi-open mandapa is entered from the eastern side. The mandapa has dwarf walls running all along its north and south sides. There are kakshasanas (seat backs) on the dwarf walls. The temple exterior is austere and minimal in ornamentation.